APPLICATION METHODDRILLFORIMPROVINGSKILLSZAPIN DANCE BASIC MOTION IN LEARNING ARTS DANCE CLASS IV SD STATE 165 PEKANBARU - Andella Putri Andella Putri; Zariul Antosa Zariul Antosa; Erlisnawati ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstrak :Issues raised in this research is to improve basic motor skills Zapin dance SDN fourth grade students 165 Pekanbaru in learning the art of dance with the application of the method Drill . Learning the art of dance in this school only to learn the material just never did practice immediately . This is due to the lack of teacher knowledge about the art of dance . In belajarpun activities , teachers only use the lecture method or explain the material. In learning the art of dance is done with the lecture method only makes children become passive in learning . So that the formulation of the problem in this research is :